Heterogeneous nuclear ribonucleoprotein A2/B1 as a novel biomarker in elderly patients for the prediction of postoperative neurocognitive dysfunction: A prospective nested case-control study - Xia, Tong; Yang, Chenyi; Wang, Xinyi; Bai, Lili; Ma, Ji; Zhao, Mingshu; Hua, Wei; Wang, Haiyun (Frontiers in Aging Neuroscience, 2022)
Background and Objective: Postoperative neurocognitive dysfunction (PND) occurs in up to 54% of older patients, giving rise to the heavy psychological and economic burdens to patients and society. To date, the development of PND biomarkers remains a challenge. Heterogeneous nuclear ribonucleoprotein A2/B1 (hnRNPA2/B1) is an RNA-binding protein whose prion-like structure is prone to mutation and hence leads to neurodegenerative diseases, but its expression changes in PND remains unclear. Here, we detect the preoperative hnRNPA2/B1 level in patients with PND, and to explore its value in the prediction and diagnosis of PND. Methods: The study included 161 elderly patients undergoing lumbar decompression and fusion in Nankai University Affinity the Third Central Hospital from September 2021 to July 2022. Neuropsychological and psychometric evaluations were performed before surgery, one week and three months after surgery to diagnose the occurrence of PND, then the peripheral blood was collected from patients before induction of anesthesia. The concentration in plasma of hnRNPA2/B1 and amyloid-β 42 were determined by enzyme-linked immunosorbent assay. The median fluorescence intensity and mRNA levels of hnRNPA2/B1 in peripheral blood mononuclear cells was detected by indirect intracellular staining flow cytometry and quantitative real-time PCR, respectively. Results: The preoperative hnRNPA2/B1 level in patients with PND was higher both in short-time and long-time follow-up. We found significantly higher concentrations of hnRNPA2/B1 in PND at 7 days after surgery (median, 72.26 pg/mL versus 54.95 pg/mL, p = 0.022) compared with patients without PND, and so as 3 months after surgery (median, 102.93 pg/mL versus 56.38 pg/mL, p = 0.012). In addition, the diagnostic efficiency of hnRNPA2/B1 for PND was higher than that of Aβ42 (AUC, 0.686 vs. 0.616 at 7 days, 0.735 vs. 0.728 at 3 months), and combining several clinical information could further enhance the predictive value (AUC, 0.707 at 7 days, 0.808 at 3 months). Conclusion: Based on the findings reported here, hnRNPA2/B1 may serve as a new and powerful predictive biomarker to identify elderly patients with PND.